More from the Romano-British Poets? A Possible Metrical Inscription from East Farleigh, Kent. (November 2019) - Mullen, Alex; Tomlin, R.S.O.
ABSTRACT: A four-line inscription in Old Roman Cursive on a pot base found in excavations in East Farleigh, Kent, in 2010 appears to be written (at least in part) in metre and has close textual similarities with examples from Binchester, Co. Durham. We describe the new text and then offer some thoughts about the possible relationship of these British texts to extant Latin verse and consider how to interpret the Kentish piece in context. Although much remains uncertain in our understanding of the text, it is a significant addition to the Romano-British corpus.